2017
DOI: 10.18596/jotcsa.346278
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterisation and DFT Calculations of Azo-Imine Dyes

Abstract: In this study, azo dyes containing an imine group were synthesised by coupling phydroxybenzylidene aniline with the diazonium salts of p-toluidine, 4-aminophenol, aniline, pchloroaniline, p-fluoroaniline and p-nitroaniline. The compounds were characterised by melting point, elemental, UV-Vis and IR analyses as well as 1 H-NMR and 13 C-NMR spectroscopies. Moreover, the experimental data were supplemented with density functional theory (DFT) calculations. The experimental data on FT-IR and UV-Vis spectra of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(42 reference statements)
2
3
0
1
Order By: Relevance
“…The -OH strecthing peak of the compounds 3 were observed at 3584-3180 cm -1 as a broad peak in agreement with the literature [6,22,26] and the theoretical value which appeared in the range of 3812 cm -1 (according to cc-pvtz basis set) and 3832 cm -1 (according to 6-311++g(2d,2p) basis set). The characteristic strecthing peaks of the azo group -N=N-are observed in the range of 1400-1550 cm -1 as a medium band in the literature [2,4,26,27]. In our study -N=N-strecthing peaks of the compounds (2-6) are observed at 1407-1442 cm -1 and 1513 -1548 cm -1 experimentally and calculated as 1496-1547cm -1 (according to cc-pvtz basis set) and 1478-1543 cm -1 (according to 6-311++g(2d,2p) basis set.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The -OH strecthing peak of the compounds 3 were observed at 3584-3180 cm -1 as a broad peak in agreement with the literature [6,22,26] and the theoretical value which appeared in the range of 3812 cm -1 (according to cc-pvtz basis set) and 3832 cm -1 (according to 6-311++g(2d,2p) basis set). The characteristic strecthing peaks of the azo group -N=N-are observed in the range of 1400-1550 cm -1 as a medium band in the literature [2,4,26,27]. In our study -N=N-strecthing peaks of the compounds (2-6) are observed at 1407-1442 cm -1 and 1513 -1548 cm -1 experimentally and calculated as 1496-1547cm -1 (according to cc-pvtz basis set) and 1478-1543 cm -1 (according to 6-311++g(2d,2p) basis set.…”
Section: Resultssupporting
confidence: 89%
“…The theoretical and experimental IR spectral data are given in Table 4. The aromatic =C-H strecthing peaks appear in the range of 3000-3100 cm -1 [2,26,27]. The aromatic =C-H strecthing peaks were observed at 3046-3134 cm -1 which are in good agreement with the calculated frequencies such as 3148-3201 cm -1 (according to cc-pvtz basis set) and 3154-3199 cm -1 (according to 6-311++g(2d,2p basis set).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The optical and electrochemical properties of the new molecule were examined by UV-Vis absorption, fluorescence emission spectroscopies, and CV. Also, the photophysical and electrochemical properties of the molecule were studied by DFT program to calculate the photophysical and electrochemical parameters (28)(29)(30).…”
Section: Twomentioning
confidence: 99%
“…Azo dyes are well-known compounds for giving color to various textile materials for many years [1][2][3][4]. These dyes play also a major role in industrial products such as printing, leather, papermaking, food industries, and drug design, except for textile dyeing [5,6].…”
Section: Introductionmentioning
confidence: 99%